PERENCANAAN PEMBANGUNAN PARTISIPATIF: STUDI TENTANG EFEKTIVITAS MUSRENBANG KEC. MUARA BADAK KAB.KUTAI KARTANEGARA - Enos Paselle (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Participatory development planning is a development approach which required the public involvement at the local level. The purpose of citizen involvement in development planning is to make sure that development programs done by government meet with the public needs. Achievement approach asserts that organization effectiveness is an ultimate goal. It assumes that organizaton is an instrument to pursue several goal, the aims of organization are common agreement or a share vision.